Design considerations for libraries providing a barrier-free library for the disabled - Mendoza, Elmer Amiel F.; Sison, Josephine C. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2001)
Libraries are the great vaults of knowledge. its purpose is to give the information needs of varied clients. Today, this purpose is being negated, because of some faults in building as well as facility designs. Mobility impaired individuals are being left out, because they cannot access the collections in the libraries. They find it hard to enter and roam around the library premises.
According to the 1995 census of population there are approximately 121,272 mobility challenged individuals in the Philippines. These are persons with paralysis or impairment of one or more limbs. Batas Pambansa Bilang 344 states that institutions like libraries should install facilities and devices to enhance the mobility of the disabled.
This study aimed to know if this law is being followed by the selected academic libraries namely: The Ateneo Rizal Library, Centro Escolar University Library, Far Eastern University Library, San Beda College Library, University of the East Library, University of the Philippines Main Library and the University of Santo Tomas Central Library. The study was conducted by performing an ocular inspection of the said subjects. Standards used in the study are adopted from the American Standards Associations specifications and Americans with Disabilities Act (ADA) guidelines for buildings. Major flows in library designs were noted, though satisfactory points were seen in other points.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Academic libraries -- Philippines -- Manila; Academic libraries -- Philippines -- Quezon City; Libraries and the handicapped -- Philippines -- Manila